Neural innervation stimulates splenic TFF2 to arrest myeloid cell expansion and cancer - Zina Dubeykovskaya; Yiling Si; Xiaowei Chen; Daniel L. Worthley; Bernhard W. Renz; Aleksandra M. Urbanska; Yoku Hayakawa; Ting Xu; C. Benedikt Westphalen; Alexander Dubeykovskiy; Duan Chen; Richard A. Friedman; et al. (Nature Communications, 2016)
During colorectal inflammation and cancer, myeloid cells accumulate in the spleen and suppress the host immunity response. In this study, the authors use a mouse model of colitis to demonstrate that upon vagus stimulation splenic memory T cells release TFF2, which suppresses the expansion of myeloid cells and cancer progression.